Three new species of Hylotribus Jekel, 1860 from Brazil, with new records and discussion of species relationships and wing variation within the genus (Coleoptera: Anthribidae) - Roza, André Silva; Mermudes, José Ricardo Miras (Zootaxa, 2019)
Recent efforts with Malaise trap sampling in Serra dos Órgãos and Itatiaia, in Brazil, allowed us to identify and describe three new species from the first locality: Hylotribus humeralis sp. nov., H. nanico sp. nov. and H. queirozi sp. nov. New records of H. plaumanni Queiroz & Mermudes, 2014 for both localities and H. sublimis Queiroz & Mermudes, 2014 for the latter are also presented. We also describe morphological variability including aptery and microptery, and male genitalia, for H. plaumanni. We produce a new key to the species and discuss the species relationships and wing variation for the genus.